Federal Democratic Republic of Nepal: An Assessment of the Rule of Law - Chhetri, Than Bahadur (Journal of Political Science, 2021)
The Rule of law, a set of principles of governance, apply to all individuals, organizations and the government itself. Democracy is a political system governed by the rule of law. No rule of law means no democratic future. This paper aims to assess the state of the rule of law under the new political setup, taking the rule of law as dependent variable and fundamental rights, corruption, open parliament and independent judiciary as independent variables. To measure the rule of law, necessary information was collected from printed and online sources. A federal democratic republic can grow healthy only when there exists the rule of law and efficient state institutions. The fundamental problems in strengthening the rule of law obstructed by the tendency of personalization and frequent intervention in state institutions, high level of corruption at policy level, poor legislative bill formulation, the controversial appointing process of the judges and the political dominations. The acceptance of international norms to address the justice and to promote human rights, adhering to the principle of inclusion and equality, maintaining transparency rule in the appointment in various constitutional bodies and keeping out of executive influence to maintain impartial and independent institutions can help in strengthening the rule of law.